Dinamika Politik Afghanistan pasca Mundurnya Uni Soviet hingga Masa Enduring Freedom, 1989-2001 - Salindri, Dewi; Widuatie, Mrr Ratna Endang; Handayani, Sri Ana; Rosyidah, Nur (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This article examines the political transformation in Afghanistan since post-Soviet occupation in 1990s up to Operation Enduring Freedom in early 2000s. Historical studies about Afghanistan with asymmetric conflict approach expected to provide alternative insight on the idea of peace and the world commitment of human rights. Results of this study are useful for further research on political dynamics, foreign intervention, conflict resolution studies, and contemporary Central Asian studies. The main discussion in this article outlines that political factionalism in Afghanistan leads to conflict because every belligerents tends to use militia forces to keep their goals. Afghans’ political circumstances become more complicated when the factions attempts to attract foreign forces to encounter each rival groups. The country become more hard to reconcile as well as the lack of efforts by belligerents to halt their rivalry.